Association between oxygen saturation and critical congenital heart disease in newborns - Lidia Halim; Muhammad Ali; Tiangsa Sembiring (Paediatrica Indonesiana, 2018)
Background Critical congenital heart disease (CCHD) is relatively common, with a prevalence of 6-8 in every 1,000 live births. This congenital anomaly is a newborn condition that would be ideally suited for a screening program, if simple and reliable methods were available. Pulse oximetry (PO) has been proposed as a screening method to detect CCHD. Objective To assess for a possible association between decreased oxygen saturation and CCHD in newborns. Methods We conducted a cross-sectional study from March 2014 to February 2015 in several hospitals in North Sumatra. Healthy, full term and post-term newborns aged 2 to 72 hours underwent pulse oximetry measurements on the right hand and one of the lower extremities. If oxygen saturation (SpO2) was ≤ 95%, the measurement was repeated 2 more times. Subjects also underwent echocardiography. Results A total of 386 newborns underwent SpO2 measurements: 377 newborns had SpO2 > 95% and 9 newborns had SpO2 ≤ 95%. Of the infants with SpO2 > 95%, 297 were excluded because their parents refused echocardiography examination. Thus, 80 newborns with SpO2 > 95% and 9 newborns with SpO2 ≤ 95% underwent echocardiography. Echocardiography revealed that 5 of 9 newborns with SpO2 ≤ 95% suffered from Tetralogy of Fallot (ToF) (3 subjects) and transposition of the great arteries (TGA) (2 subjects). One infant with SpO2 > 95% had ventricular septal defect (VSD), as detected by echocardiography. Oxygen saturation ≤ 95% had significant association with CCHD (P<0.001). Conclusion Decreased oxygen saturation has a significant association with critical congenital heart disease in newborns.